PENGARUH MUTU PELAYANAN TERHADAP KEPUASAN PASIEN: (STUDI KASUS PADA PASIEN RAWAT JALAN DI RUMAH SAKIT MATA BANDUNG EYE CENTER) - Mira Veranita; Hani Hatimatunnisani (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2023)
This study uses a quantitative descriptive approach to analyze the data which includes testing the validity, reliability, Spearman Rank correlation, and the coefficient of determination. Questionnaires, observations, and literature searches were used to collect data from 94 patients in the Outpatient Unit of the Bandung Eye Center Eye Hospital. The results of this study indicate that the quality of health services at RSM Eye Center Bandung is very good with a score of 85.5 percent. The satisfaction level of outpatients produces a value of 85%, which means that patient satisfaction is very good. The Spearman Rank correlation test is 0.631, which means it is strong at the interval 0.60 – 0.799 and is tested on the coefficient of determination giving a figure of 40%, meaning that 60% is still influenced by other factors.